PERLINDUNGAN HUKUM TERHADAP PELAKU USAHA JUAL BELI ONLINE DENGAN METODE PEMBAYARAN KREDIT DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH DAN HUKUM POSITIF (Studi di Vivi Shop Media Elektronik Whatsapp) - Fitri Afifah; Liky Faizal (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
In the view of Islamic law, legal protection efforts that can be given to business actors related to bad faith behavior carried out by the buyer, one of which can be resolved by consultation, so that the relationship between the parties can certainly be lived well compared to cases handled in court. In positive law, the form of protection related to the law of online shop business actors who suffer losses due to the malicious intent of customers is based on the GCPL law, which also protects the rights of business actors to create a healthy trade process. As for the equations of Islamic law and positive law related to online buying and selling practices through payment methods, namely credit that occurs at Vivi Shop with Whatsapps electronic media, the problem is resolved by peace between the two parties. This is also consistent with the theory used by researchers in analyzing the case with the theory of Ishlãh. As we know, Ishlãh is an agreement to settle a dispute between two parties to a dispute peacefully, but the buyer still has the obligation to pay the arrears of installments for the goods for which he is responsible. While the difference in Islamic law and positive law related to the practice of buying and selling online with a credit payment system is when in Islamic law the problem can be resolved only between the business actors and buyers, while in positive law when the problem if there is no bright spot between the two parties, the business actors can file complaints to the Consumer Dispute Resolution Agency in accordance with Article 6 of Law Number 8 of 1999 to demand justice and responsibility for the losses suffered by business actors for actions taken by consumers.